2011
DOI: 10.3989/scimar.03564.29a
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the effects of a trawling ban on diet and trophic level of hake, <i>Merluccius merluccius</i>, in the southern Tyrrhenian Sea

Abstract: SUMMARY: This study assesses the effects of a trawling ban on the diet and trophodynamics of the hake Merluccius merluccius by comparing stomach contents and stable isotopes (δ 15 N and δ 13 C) in two trawled gulfs and one untrawled gulf in northern Sicily (western Mediterranean). Comparisons were made for three size classes of hake encompassing 60 to 410 mm total length. Fish were collected from 50 to 200 m depth on muddy bottoms. The diets of hake of small and medium size were similar overall but more select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 54 publications
7
23
0
Order By: Relevance
“…Considering isotopic ratios, juveniles exhibited lower values than adults. This change could be explained by the ontogenetic change of diet (Ferraton et al, 2007;Harmelin-Vivien et al, 2012a,b;Sinopoli et al, 2012). The correlation between δ 15 N and length observed here is consistent with observations from other studies in the Mediterranean Sea or the Atlantic Ocean (Harmelin-Vivien et al, 2012a;Chouvelon et al, 2014).…”
Section: The Rhône River Main Driver Of the Pattern In The Gulf Of Lsupporting
confidence: 93%
See 1 more Smart Citation
“…Considering isotopic ratios, juveniles exhibited lower values than adults. This change could be explained by the ontogenetic change of diet (Ferraton et al, 2007;Harmelin-Vivien et al, 2012a,b;Sinopoli et al, 2012). The correlation between δ 15 N and length observed here is consistent with observations from other studies in the Mediterranean Sea or the Atlantic Ocean (Harmelin-Vivien et al, 2012a;Chouvelon et al, 2014).…”
Section: The Rhône River Main Driver Of the Pattern In The Gulf Of Lsupporting
confidence: 93%
“…Since their growth rate is slower (de Pontual et al, 2006;Mellon-Duval et al, 2010), males stay longer on the shelf, and are predominantly harvested, which explains the imbalanced sex-ratio and the predominance of female hake in the Gulf of Lions. The high trophic position of hake and its predominance in Mediterranean fisheries (Aldebert et al, 1993;Harmelin-Vivien et al, 2012a;Sinopoli et al, 2012;Bănaru et al, 2013) have made necessary extensive assessment of the contamination patterns. Recent studies in the Gulf of Lions identify sex, growth rate, reproduction and diet as key factors to explain the contamination patterns (Bodiguel et al, 2009a(Bodiguel et al, , 2009bMellon-Duval et al, 2010;Cossa et al, 2012;Harmelin-Vivien et al, 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…Sci., 17/2, 2016, 496-507 503 Our overall results indicate that the trophic level does not increase with the presence of the protection itself. This conclusion is in line with previous studies indicating that trophic level does not necessarily increase with protection and in some cases it can even decrease (Deudero et al, 2004;Vizzini & Mazzola, 2009;Sinopoli et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…The ecosystem effects of the trawl ban assessed through investigation of the trophodynamics of two commercial fish species in the Gulf of Castellammare and in the two controls did not yield clear and homogeneous results (Fanelli et al, 2010;Sinopoli et al, 2012). Badalamenti et al (2008) found only limited effects of trawling on the trophodynamics of three .…”
Section: The Effects Of Mmas On Fisheriesmentioning
confidence: 96%